Bioactive Hydrogel Marbles - Álvaro J. Leite (Nature Portfolio, 2018)
Abstract Liquid marbles represented a significant advance in the manipulation of fluids as they used particle films to confine liquid drops, creating a robust and durable soft solid. We exploit this technology to engineering a bioactive hydrogel marble (BHM). Specifically, pristine bioactive glass nanoparticles were chemically tuned to produce biocompatible hydrophobic bioactive glass nanoparticles (H-BGNPs) that shielded a gelatin-based bead. The designed BHM shell promoted the growth of a bone-like apatite layer upon immersion in a physiological environment. The fabrication process allowed the efficient incorporation of drugs and cells into the engineered structure. The BHM provided a simultaneously controlled release of distinct encapsulated therapeutic model molecules. Moreover, the BHM sustained cell encapsulation in a 3D environment as demonstrated by an excellent in vitro stability and cytocompatibility. The engineered structures also showed potential to regulate a pre-osteoblastic cell line into osteogenic commitment. Overall, these hierarchical nanostructured and functional marbles revealed a high potential for future applications in bone tissue engineering.